2018
DOI: 10.1007/s10853-018-3113-7
|View full text |Cite
|
Sign up to set email alerts
|

3D microstructure of magnesium potassium phosphate ceramics from X-ray tomography: new insights into the reaction mechanisms

Abstract: Magnesium potassium phosphate ceramics are chemically bonded ceramics employed as biomaterials, in nuclear waste encapsulation and for concrete repair. The microstructure dictates material performance and depends on the raw mix composition. Synchrotron X-ray computed microtomography was employed to describe the 3D microstructure and its time evolution during hardening and gain insights into the reaction mechanisms. Any excess water with respect to the stoichiometry of the reaction brought about an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
(111 reference statements)
1
21
0
Order By: Relevance
“…Crystallization has been proposed to occur close to the surface of the MgO grains, on their surface, or also partly at random in the amorphous mass . Recently, reaction kinetics analysis and mCT indicated that more than one process may be active during the setting reaction, with each single contribution changing in time and in function of the mix formulation . Because MgO annealed at lower temperature possesses a higher specific surface area, a more reactive MgO should favor the development of more K‐struvite nuclei, as confirmed by higher initial crystallization rates .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Crystallization has been proposed to occur close to the surface of the MgO grains, on their surface, or also partly at random in the amorphous mass . Recently, reaction kinetics analysis and mCT indicated that more than one process may be active during the setting reaction, with each single contribution changing in time and in function of the mix formulation . Because MgO annealed at lower temperature possesses a higher specific surface area, a more reactive MgO should favor the development of more K‐struvite nuclei, as confirmed by higher initial crystallization rates .…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, reaction kinetics analysis and mCT indicated that more than one process may be active during the setting reaction, with each single contribution changing in time and in function of the mix formulation. 7,12,17 Because MgO annealed at lower temperature possesses a higher specific surface area, a more reactive MgO should favor the development of more K-struvite nuclei, as confirmed by higher initial crystallization rates. 7,12 According to the mechanism of microstructural evolution described above, it may be argued that with more crystals, more pores (with D > 2.7 μm) should form as it is, in fact, observed (8728, 5161 and 4734 in the VOI of the samples MPC_1500_15 days, MPC_1550_15 days and MPC_1600_15 days, respectively), and illustrated in Figure 2.…”
Section: Role Of Mgo Reactivitymentioning
confidence: 96%
See 3 more Smart Citations